CALCIUM, CREATININE AND URINARY PHOSPHATE/CREATININE RATIO CONCENTRATIONS IN NEONATES OF VARIOUS GESTATIONAL AGES - O. I. Fomina; T. A. Kuznetsova; A. V. Shulga (Union of pediatricians of Russia, 2014)
Objective: specify peculiarities of calcium and phosphates excretion in neonates of various gestational ages and types of feeding in neonatal period. Patients and methods. Calcium-creatinine (Ca/Cr) and phosphate-creatinine (P/Cr) ratio concentrations were determined in 96 healthy neonates of 38-40 weeks of gestational age and 146 premature infants of 28-37 weeks of gestational age of various types of feeding. Results. The Ca/Cr ratio concentration in healthy term infants in the early neonatal period amounted to 0.9-2.2 (median - 1.8), the P/Cr ratio concentration - 0.8-2.1 (median - 1.6). The Ca/Cr ratio concentration in premature infants (28-37 weeks of gestational age) amounted to 0.9-2.4 (median - 1.9), which is comparable to this parameter's value in term infants. The P/Cr ratio concentration amounted to 0.7-3.1 (median - 2.4), which exceeds this parameter's value in term infants. The lesser the gestational age and birth weight, the higher the Ca/Cr and P/Cr ratio concentrations. The authors revealed hypercalciuria and hyperphosphaturia in premature infants with a very low body weight fed with specialized formulas. Conclusions. Use of specialized formulas in small premature infants (gestational age < 33 weeks) with VLBW results in excessive calcium and phosphates excretion. It is reasonable to monitor their concentrations using a non-invasive and informative method of determining Ca/Cr and P/Cr ratios. Feeding of premature infants with BW > 1,500 g with breast milk only (in case of the mother's adequate lactation) allows avoiding hypercalciuria and hyperphosphaturia and preventing risk of a renal pathology.